Corporate Social Responsibility in the Greek Mining and Quarrying companies - Fragkoulis, Dimitrios; Koemtzi, Maria (International Conference on Business and Economics - Hellenic Open University, 2023)
This paper aims to investigate the diffusion of the concept of Corporate Social Responsibility (CSR) and the degree of implementation of CSR practices among the Greek Mining and Quarrying Companies. A research study was conducted through a structured questionnaire among the ISO 9001 certified Greek Mining and Quarrying Companies. CSR appears to be very important for large companies which are able to allocate resources for the required CSR actions. Results show that most of the financial resources available for CSR actions are related to the environment and that respondents expect that through CSR actions they gain better relationships with the local community and the general business environment, they achieve improved employee performance, and they attract and maintain high-potential employees. Participants in the research consider bureaucracy, lack of knowledge, the small size of business and the implementation costs as the main inhibitors for the achievement of the CSR principles. The research of this work was limited to the Greek mining companies that are certified according to ISO 9001. Future research could be conducted on the CSR awareness of the non-certified companies as well. The study may help managers of the mining companies to focus on specific CSR elements when they decide to follow CSR principles. The implementation of the CSR principles in the mining industry has attracted considerable attention in the CSR literature and this study is an attempt to assess the concept and the benefits of CSR within Greek mining sector. JEL Classification code: M14. Key words: Corporate Social Responsibility; CSR; Mining and Quarrying; Greece